PENGARUH INFORMASI LABA TERHADAP KOEFISIEN RESPON LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA TAHUN 2011-2014) - Sari, Novi Liya; Daud, Rulfah M. (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The purpose of this research is to examine and analyze the influence of the net income (PEPS) and income from operating activities (POP) to earnings response coefficient manufacturing company in 2011-2014. The research type used is a correlational study by purposive sampling method. The total research sample is 24 manufactur company.The data used in this research is secondary data which got from the financial statements which published by the center stock market reference at the Indonesia Stock Exchange. The multiple regression analysis model is used to test the hypothesis while processing the data using the statistical program SPSS 21. The results of this research shows that the (1) net income (PEPS) and income from operating activities (POP) simultaneously influance to earnings response coefficient (2) net income (PEPS) has negative influance to earnings response coefficient (3) income from operating activities (POP) has positive influance to earnings response coefficient.Keyword: Earnings Response Coefficient, Net Income (PEPS), Income from Operating Activities (POP)